PENGELOLAAN ARSIP KONVENSIONAL PADA UNIT TRANSACTION PROCSSING BANK BTN KC. BANDUNG - Rahmanesa, Abdur; Supyansuri , Cahyadi (NIAGARA Scientific Journal, 2025)
This research aims to determine the success rate of conventional archive management in the Transaction Processing unit of Bank BTN KC. Bandung. The method used in this research is descriptive qualitative, with data collection techniques through literature studies, observations, interviews, and studying documentation. The focus of the research lies in the process of conventional archive management, starting from creation, storage, to destruction of archives. The result of the research indicate that the management is running quite well. There are several obstacles in searching for physical archive documents, increasing paper usage, and limited storage space. To overcome these obstacles, several alternative steps are implemented, including the use of the work unit daily inspection sheeta and manual transaction registration book as tools to search for physical archive documentation